Covid-19 Non-natural Disaster Mitigation: A Literature Review - Faisal, T. Iskandar; Khaira, Nuswatul; Magfirah, Magfirah; Veri, Nora (Poltekkes Kemenkes Palu, 2024)
Non-natural disasters are defined as types of disasters that occur due to non-natural causes, including technological failure, modernization failure, epidemics, and disease outbreak. One type of non-natural disaster that occurs in society is the Covid-19 pandemic. There is a need for disaster mitigation due to Covid-19 to minimize the risk of impacts that will or have occurred. This article was prepared to find out the diversity of disaster mitigation that has been implemented all this time. The research method used is literature study or a type of academic survey research where data is obtained from government website reports, expert studies, scientific literature, and research institute studies. This review describes disaster mitigation methods that have been implemented by individuals, schools, communities, hospitals, and governments to minimize the impact of the Covid-19 pandemic. There is cooperation between individuals, communities, and the government in realizing the fruitful implementation of non-natural disaster mitigation, especially COVID-19. Policies that are not on target and do not focus on handling the Covid-19 pandemic will not be able to minimize deaths from Covid-19, and the socio-economic impact of the spread of the virus will be massive and serious.